Evaluation of the Do Bugs Need Drugs? Program in British Columbia: Can We Curb Antibiotic Prescribing? - Rachel M. McKay; Linda Vrbova; Elaine Fuertes; Mei Chong; Samara David; Kim Dreher; Dale Purych; Edith Blondel-Hill; Bonnie Henry; Fawziah Marra; Perry RW. Kendall; David M. Patrick (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: Antibiotic resistance is accelerated by the overuse of antibiotics. Do Bugs Need Drugs? is an educational program adapted in British Columbia to target both the public and health care professionals, with the aim of reducing unnecessary prescribing. The current article presents a descriptive evaluation of the impact of the program over the first four years.